THE EFFECT OF INSTAGRAM ACCOUNT MOTIVATIONAL POSTS @RINTIKSEDU ON THE QUALITY OF LIFE OF HIS FOLLOWERS - Ramdhani, Desy Ainur; Mauldini, Saadah; Bahtiar, Dandi; Agustina, Aminah (JURNAL SIGNAL, 2024)
Instagram is one of the most popular social media platforms in Indonesia because internet users have reached 210 million people. This study refers to the Instagram account @rintiksedu which uploads a lot of motivational posts that can build the quality of life of followers through the posts uploaded. The purpose of this study is to find out how much influence the motivational posts on the Instagram account @rintiksedu are related to self-expression, self-expression, enhancement and cognitive motives as stated by Fradsen on the quality of life of followers. In this study, the researcher used a quantitative descriptive approach with a simple linear regression test data analysis technique, while the population in this study were followers of the Instagram account @rintiksedu. The sampling technique used is purposive sampling using the Slovin formula. Data collection is used by distributing questionnaires to 100 respondents who are active followers of @rintiksedu. The results showed that there was a positive and significant influence between motivational posts on the Instagram account @rintiksedu related to self-expression, self-enhancement and cognitive motives on the quality of life of followers, with a fairly strong correlation coefficient.